Experimental taphonomy of velvet worms (Onychophora) and implications for the Cambrian "explosion, disparity and decimation" model - Julián Monge-Nájera; Hou Xianguang (Revista de Biología Tropical, 2002)
Experimental preservation of velvet worms (phylum Onychophora), a very rare but evolutionarily important group that has existed for more than 500 million years, showed that the absence of bucal parts, adhesive-expelling organs, gonopore, eyes, legs, claws, annulation and papillation in fossils may not represent absence in the living animals. In fossils, leg thickness and claw orientation can be unreliable. The experiments indicate that not only absence, but even presence of certain structures can simply be the result of tissue decomposition. Computer-aided photorealistic reconstructions of fossil onychophorans are presented. We recommend future researchers to conduct taphonomy experiments specially before analysing unusual fossils. La preservación experimental de los gusanos "aterciopelados" u onicóforos (Phylum Onychophora), un grupo poco común pero evolutivamente importante que ha existido por más de 500 millones de años, mostró que la ausencia de partes bucales, glándulas secretoras de adhesivo, gonoporo, ojos, patas, garras, anulación cuticular y papilas en los fósiles, puede no representar la ausencia de tales órganos en los organismos vivos. No son contables el grueso de las patas y la orientación de las garras (uñas), pues se modifican durante la preservación. Los experimentos indican que no sólo la ausencia, sino también la presencia de ciertas estructuras pueden ser simplemente resultado de la descomposición de los tejidos. Se presentan reconstrucciones fotorrealistas computarizadas de onicóforos fósiles. Para futuras investigaciones, recomendarnos conducir experimentos tafonónúcos previos al análisis del material preservado, especialmente antes de analizar fósiles poco comunes.